Literacy Media Counseling Program, Increasing Parent Skill on Parental Mediation and Parental Gadget Co-Viewing on Students of Al-Hikmah Suko Sidoarjo - Syifa Syarifah Alamiyah; Ahmad Zamzamy; Resa Rasyidah (Future Science)
The purpose of this program is to raise awareness of the dangers of excessive media usage on children and to improve parenting skills related to children media activities. Considering that the Information and Communication Technology has become an important part of people's lives from the various aspect. Even recently children have known and become an expert in using gadgets. In this case, the role of parents is needed to be wise in providing communication media to children. Based on preliminary observations, the use of gadgets by children was due to lack of supervision and restrictions by their parents. To overcome these problems, the solution offered is to organize a Media Literation counseling addressed to parents of Al-Hikmah Kindergarten with the theme of Literacy Media: Improving Parents Skills in parental mediation and parental co-viewing of the use of Gadgets on kindergarten students. This activity used counseling methods to increase awareness of parents' knowledge of the dangers of excessive use of digital media with methods of exposure, case study and discussion and Question and Answer. So that parents have a strong awareness and willingness to limit and accompany the use of media in children. In addition, through the training method, parents will be equipped with skills to calculate and design the number and content of media that appropriate to the age of the child by using the method of